2018
DOI: 10.21767/2248-9215.100050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Angiographic Coronary Slow Flow Phenomenon and Subfoveal Choroidal Thickness: What is The Effect of Atorvastatin Therapy?

Abstract: Objective: Although the pathophysiological mechanisms underlying coronary slow flow (CSF) phenomenon still remains uncertain, the microvascular dysfunction has been first implicated. The CSF phenomenon may not only affect the coronary arteries but it may also be a part of vascular problem that affect other arteries. The aim of the present study is to evaluate the relationship between CSF phenomenon and subfoveal choroidal thickness (SFCT) and to investigate the effect of short-term atorvastatin therapy on SFCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Atorvastatin is significantly associated with increased CT 42 while fluvastatin and pravastatin are significantly associated with decreased CT 43 . SFCT significantly increased from baseline after 2 weeks of atorvastatin treatment in patients with abnormal coronary angiography findings 42 .…”
Section: Resultsmentioning
confidence: 88%
“…Atorvastatin is significantly associated with increased CT 42 while fluvastatin and pravastatin are significantly associated with decreased CT 43 . SFCT significantly increased from baseline after 2 weeks of atorvastatin treatment in patients with abnormal coronary angiography findings 42 .…”
Section: Resultsmentioning
confidence: 88%
“…However, there are some important aspects of the above-mentioned studies that may justify the disparity. First, in addition to the fact that the number of patients studied was slightly lower than in our research, the inclusion criteria for two of the studies was the presence of coronary slow-ow phenomenon 19,20 , the de nition of which excludes the presence of evident obstructive disease and which, therefore, would preclude comparison of the results obtained. Secondly, another of the studies associated the presence of CAD with a decrease of capillary density and choroid ow in general, without referring to thickness 21 .…”
Section: Discussionmentioning
confidence: 95%
“…Although there is growing body of evidence to support the theory that changes in CT may be of prognostic use, controversy still exists in this regard 18 . Recent studies have suggested that in CAD there is a probable relationship between a decrease in capillary density and choroid blood ow, as well as with a general thinning of choroid 2,[19][20][21] . Such reports contradict the ndings of our study, which indicate that an increase in choroidal thickness is associated with the presence of coronary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant negative association between the severity of coronary artery stenosis and vessel density, including the choroid capillary fovea and choroid capillary flow. However, Doğan et al [ 36 ] and Kanar et al [ 37 ] found a thinner choroid in patients with coronary slow-flow phenomenon compared to healthy volunteers. Moreover, Schuster et al [ 26 ] assessed the correlation between CTh and cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%